Kondisi Sosial Ekonomi Masyarakat di Desa Dahiango Kecamatan Mawasangka Kabupaten Buton Tengah - Asni Siri; Abdul Jalil (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2022)
This study aims to determine the socio-economic condition of the community in Dahiango Village, Mawasangka District, Central Buton Regency, which generally talks about health, education, community work, and community housing conditions. This research uses the theory of Human Ecology by Rambo by using qualitative methods. The results of the research on the social conditions of the community, the educational condition of the community is still very lacking, so they only work as field farmers, laborers, wood bearers and traders, health facilities for the Dahango community are not adequate, in the village there is already a Polindes building but there are no facilities, the community only can check his health twice a month. Economic Conditions For the work of the people of Dahiango Village, they have potential, they have local wisdom values ??such as making baskets from forest rattan, but the community has problems in marketing their products, lack of community education so that they do not have expertise in marketing their baskets, lack of traders who enter in Dahiango Village so they only sell it to the people in the village.